MODEL INTEROPERABILITAS ANTAR APLIKASI E-GOVERNMENT - Istiyanto, Jazi Eko; Sutanta, Edhy (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
Interoperability between information systems is an urgent problem to be solved in the development of e-Gov in Indonesia. This is caused by the need for increasing the data multisectoral policy-making in order to solve problems involving data from the inter-related sectors. While the state government application in the current environment, are still largely sectoral, in isolation, can not communicate with each other, and heterogeneous. Interoperability between e-Gov applications become important things to be sought the solution to the problem of developing e-Gov in Indonesia are not protracted. This paper is a review of the literature reveals the development of e-Gov in Indonesia, the interoperability problems encountered, and how the model of interoperability between e-Gov built to implement a web services models.